PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DAPAT MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 125 PEKANBARU - Pingki Oktora Sari Oktora Sari; Hendri Marhadi Hendri Marhadi; Lazim N Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The problems in this research is the low learning outcomes IPS Elementary School fourth grade students 125 Pekanbaru, the average grade of 60, 40 with the KKM IPS was 70. This research aims to improve learning outcomes IPS Elementary School fourth grade students 125 Pekanbaru implement cooperative learning model Make a Match. The research was conducted on 10 March 2015 to 28 March 2015 were carried out by 3 cycles. This thesis presents the results obtained from the study before action replay value with an average of 60, 40, rose in the first cycle with an average of 67.2. In the second cycle increased by an average of 75.6 and the third cycle increased by an average of 80.8. Aktiviats teacher in the learning process the first cycle of the first meeting and the second meeting of the 54.2% increase to 62.5%.Second cycle of the first meeting and the second meeting of the 75% increase to 83.33%.Cycle III first meeting and the second meeting of the 87.5% increase to 95.82%.Aktiviats students the first cycle of the first meeting with the average of 54.2% and the second meeting increased to 58.33%. The first meeting of the second cycle with an average of 66.67% and the second meeting increased to 75%. The first meeting of the third cycle with an average of 83.33% and the second meeting increased to 95.82%.From the research results in the fourth grade Pekanbaru 125 countries prove that the implementation of cooperative learning model Make a Match can improve learning outcomes IPS Elementary School fourth grade students 125 Pekanbaru.Key Words: Cooperative Make A Match students,learning outcomes.